DISABILITY LEARNING TOOL: BRUSHING-TEETH USING MUSIC FOR AUTISM - Othman, A. (2011)
This research is an attempt of combining music with the 3D animation technique in order to develop a disability-learning tool which can be used as one of occupational therapy for autism children. Autism is a developmental disability of the brain, much like dyslexia, mental retardation, or attention deficit disorder that often makes it hard to communicate with and relate to others. The treatment that we are going to apply in our research is related to the occupational therapies which involved music, multisensory stimulant and computer usage. Occupational therapy assists autistic people in developing the skills for daily job such as brushing teeth. Music can stimulate brain and help individuals with a wide range of cognitive and emotional challenges to improve their ability to function. Music primarily can help autism children improve their observable level of functioning and selfreported quality of life in various domains such as cognitive functioning, motor skills, emotional and effective development, behavior and social skills. The problem that we are trying to overcome by doing this project is the independence among autism children. At the autism centre where we did our research, they are manually taught by parent or teachers and they have to teach the same thing every day. For example, the teachers have to show them every day on how to brush teeth using the teeth set and the big tooth brush. They seem cannot remember all the steps. In this research, by collaborating these elements, we try to develop a 3D animation disability-learning tool to help in stimulating independence in autism children. Music is included in the animation as part of the treatment. The objectives of this projects are first to investigate and analyze the acceptance of different types of music among autism children. Our second objective is to develop a 3D animation that show steps in brushing teeth according to the beat of the selected music. The third objective is to analyze the effectiveness of the application in stimulating remembrance brushing technique skills. 3D animation is a technique that can visualize characters or movement as same as in the real life. The current technology of 3D animation exist today is amazing. This application which is called Disability Learning Tool: Brushing-Teeth Using Music for Autism has been tested to a group of autism children with mild cases and has shown positive result. It can be seen that the independence in the autism children gradually increased. However, there’s a lot more to do for further improvement and we are going to look into each of these weaknesses in detail.